Japan: Shadow WTO Agricultural Domestic Support Notifications - Godo, Yoshihisa; Takahashi, Daisuke (International Food Policy Research Institute, 2008)
The purpose of this paper is to provide a comprehensive review of Japan’s agricultural domestic policy since 1995 in the context of the current international negotiations in the WTO Doha Round, which has as one aim further reductions of trade-distorting support among member countries. An overwhelming majority of farmers in Japan own small plots of rice paddy fields and earn their living mainly on their off-farm income. They go out into rice paddy fields in their spare time as a subsidiary business. Traditional small farming communities are powerful voting groups that seek to maintain their political power. By exerting political pressures on the authorities, farmers can obtain large returns through the manipulation of farmland use regulations, even though such manipulation causes social harm by preventing efficient land use. These inefficiencies in land use are a major reason why Japan is the only country whose food self-sufficiency rate keeps declining in spite of its heavy agricultural protection. In this sense, Japan is in sharp contrast to European and North American countries, where heavy agricultural domestic supports have resulted in an increased output of agricultural commodities and subsequent distortions in international markets. Apparently, Japan’s attitude towards agricultural domestic policy reform is one of compliance with the WTO, which requests member countries to reduce their Aggregate Measure of Support (AMS) through trimming trade-distorting (amber box) support and/or transforming traditional-type agricultural subsidies to decoupled-type ones. Japan reduced its amber box support by nearly 80 percent between 1995 and 2000. This drastic reduction is mainly attributable to Japan’s removal of rice from the amber box in 1998. In addition, following the WTO’s principle of decoupling, Japan launched an extensive agricultural subsidy reform in 2007. This paper, however, shows the ironical realities of Japanese agricultural policy. Neither a sharp reduction of amber box support nor Japan’s 2007 reform necessarily mean there will be a reduction of trade-distorting effects. On the contrary, the 2007 reform may in fact stimulate domestic rice production. In 2007, Japan’s AMS is as little as 18 percent of its commitment level from the Uruguay Round WTO agreements. In addition, this paper projects that Japan’s overall trade-distorting support (OTDS) for 2013 will be 469 billion yen, which is much less than the limit of 1,635 billion yen that is proposed in the modalities under discussion in July 2008 for the WTO Doha Round. Thus, the WTO Doha Round negotiations on domestic support policy are unlikely to restrict Japan’s domestic agricultural support policy.